Robert Morrison and the Anglo-Chinese College. (November 2021) - Su, Ching
Abstract : Mainly based on archival materials of the London Missionary Society (LMS) and published materials dating from around the time the Anglo-Chinese College (ACC) was established in Malacca, this paper discusses the different roles played by Robert Morrison in connection with the ACC before and after its establishment – as founder, fundraiser, decision-maker and teacher. The paper explores why and how he established the ACC, as well as how he maintained, led and managed it. Difficulties facing the ACC in Malacca and its achievements are also described.*